2014
DOI: 10.1186/1471-2490-14-27
|View full text |Cite
|
Sign up to set email alerts
|

The effect of smoking on spontaneous passage of distal ureteral stones

Abstract: BackgroundAnimal studies have shown that nicotine affects the peristalsis of the ureter. The aim of the study is to analyze the effect of smoking on spontaneous passage of distal ureteral stones.Methods88 patients in whom distal ureteral stone below 10 mm diameter diagnosed with helical computerized tomography enhanced images were reviewed. Patients were grouped as either smokers (n:33) or non smokers (n:50). Follow-up for spontaneous passage of stones was limited with 4 weeks. Patients did not receive any add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Lifestyle factors, such as smoking habits and sexual intercourse, have also been investigated in recent years as potential factors of spontaneous passage. Fazlıoğlu et al reported similar SP ratios in < 4 mm distal ureter stones for smokers and non-smokers, but for ≥ 4 mm distal ureter stones, the SP ratio was reported to be lower in smokers [25]. In another study, Bayraktar et al investigated three groups of patients with 5-10 mm distal ureteral stones receiving different treatments.…”
Section: Discussionmentioning
confidence: 96%
“…Lifestyle factors, such as smoking habits and sexual intercourse, have also been investigated in recent years as potential factors of spontaneous passage. Fazlıoğlu et al reported similar SP ratios in < 4 mm distal ureter stones for smokers and non-smokers, but for ≥ 4 mm distal ureter stones, the SP ratio was reported to be lower in smokers [25]. In another study, Bayraktar et al investigated three groups of patients with 5-10 mm distal ureteral stones receiving different treatments.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, we found the G/A + A/A genotype carriers had a higher causative effect in subgroup of age<50, ever smoking, ever drinking, creatinine normal, and high uric acid. In the past studies, age, smoking consumption, alcohol consumption, and renal function had been shown to play an important role in the formation of urolithiasis. Our results suggest that age, smoking consumption, alcohol consumption, creatinine, and uric acid may play a synergistic role with rs12654812 gene polymorphism and strengthen the genetic effect of nephrolithiasis.…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine is said to alter ureteric peristalsis, probably through its effect on the cholinergic receptors present in the ureter. Recently, Fazlioglu et al [12] reported that smoking had no effect. Similarly, we found no significant difference between smokers and non-smokers in the present study.…”
Section: Discussionmentioning
confidence: 99%